PEMBENTUKAN PORTOFOLIO OPTIMAL INVESTASI MENGGUNAKAN MODEL MARKOWITZ DAN MODEL INDEKS TUNGGAL PADA ASET BEBAS RISIKO DAN ASET BERISIKO - Abdul Gafur (Journal of Management and Innovation Entrepreneurship (JMIE), 2024)
Optimal Portfolio is one way that can be used to determine stock portfolios that generate large returns with the smallest risk. The purpose of this study is to determine the optimal portfolio of risk-free assets and risk assets using the Markowitz Model, Single Index Model and portfolio performance by comparing the resulting rate of return and risk. The research sample used was LQ 45 shares listed on the Indonesia Stock Exchange from August 2014 to July 2019.    The sampling technique used was purposive sampling technique, namely the selection of data based on certain criteria in order to obtain a sample of 29 listed companies. The method used is to use the Markowitz Model, the Single Index Model and portfolio performance. From the optimal portfolio formation based on the Method, there are 9 shares included in risk free assets and 20 shares included in risk assets. The results of the analysis show that by using the Single Index Model the return from the optimal portfolio produced is higher than using the Markowitz Model, as well as the risk generated on the Single Index Model is smaller than using the Markowitz Model both on risk-free assets and risk assets, this is assured with the results obtained from portfolio performance.